Post cholecystectomy common bile duct dilatation: a study from upper hills of Himachal Pradesh, India - Sood, Rajan; Singh, Rinku; Chawla, Sumit (International Journal of Research in Medical Sciences, 2020)
Background: Relationship between cholecystectomy followed by postoperative dilatation of the common bile duct is uncertain. Various studies have shown variable results regarding the dilatation of common bile duct after cholecystectomy. Methods: This study was a 1-year prospective study conducted at IGMC, Shimla with consent and ethical approval from the committee. Total 50 cases of symptomatic cholelithiasis belonging to either sex admitted in Surgical Wards of IGMC Shimla for elective surgery were selected for the present study. Cholecystectomy was done in all cases, after doing all the investigations. Results: The mean preoperative CBD diameter in the study group was 4.2mm, 48 hours postoperatively was 5.58mm and at 1-month interval following cholecystectomy was 6.02mm, so the mean postoperative diameter observed was (6.02+5.58=5.8mm). Conclusions: Significant dilatation does occur in CBD which is purely compensatory as there was no evidence of any pathological dilatation. This dilatation occur only in early post-operative period till the CBD adapts to contain bile equal to the Gall Bladder.